Interpreting Rock-Cut Grave Cemeteries: The Early Medieval Necropolis and Enclosure of São Gens, Portugal. Issue 2 (3rd July 2017) - Brookes, Stuart; Tente, Catarina; Prata, Sara
Abstract : EXCAVATION AT SÃO GENS (Guarda district) in central Portugal has revealed an early medieval rock-cut grave cemetery and settlement, along with Roman and prehistoric evidence. The site presents an exceptionally rich palimpsest of archaeological monuments. This paper reviews the findings and seeks to address the problem of interpreting rock-cut grave cemeteries, by describing a spatial analytical methodology that draws on comparisons with early medieval cemeteries in England, as a means of enhancing the information deficit of such necropolises. In the light of these analyses, an interpretation of the São Gens site is offered in conclusion.